The vernacular church music of William Byrd : a reappraisal of chronology, authenticity and context - Johnstone, Andrew (Trinity College (Dublin, Ireland). Department of Music, 2014)
This aim of this thesis is a unified reappraisal of the vernacular church music of William Byrd (c.1540-1623). Specific objectives include the elimination of opera dubia, the distinguishing of adapted consort works from original verse compositions, and the evaluation of developments in Byrd's polyphonic language within the vernacular genres. Attention is also paid to the question of how Byrd's recusancy might have impinged on his composition of Protestant music.
Keywords: Music, Ph.D.; Ph.D. Trinity College Dublin.